Referral to a probation centre as an educational measure - Krzysztof Stasiak (Probacja, 2023)
Referral to a probation centre is an educational measure that is adjudicated on average against 2% of juveniles. It is most often applied to juveniles who show behavior indicative of their demoralization (in about 70%). In the context of the changes that have taken place in the phenomenon of social maladjustment (an increase in the behaviors of juveniles that are indicative of their demoralization; in 2020, in 56% this was the reason for applying educational measures to them), referring a minor to a probation center appears to be one of the better means of influencing a minor, as the centre is a facility that has extensive experience in working with demoralized persons. This argues for further development of probation centres, both in organizational and methodical spheres. The new Act on the Support and Re-socialisation of Juveniles, which replaced the Act on the Proceedings in Juvenile Matters, modifies the basic purpose of a probation centre and transforms it from a primarily preventive facility into a typical educational and re-socialisation facility. The proposed changes go in the right direction, as they strengthen probation centres in organisational terms. However, it is questionable whether it is appropriate for this Act to regulate the rules for the creation, abolition and organisation of the centre, as these issues are of a systemic nature. A probation centre is undoubtedly an element of the probation service, for which reason the Probation Officers Act seems a more appropriate place to regulate such issues.